2019
DOI: 10.1088/1748-9326/ab30e5
|View full text |Cite
|
Sign up to set email alerts
|

Sediment accumulation expectations for growing desert cities: a realistic desired outcome to be used in constructing appropriately sized sediment storage of flood control structures

Abstract: Many rapidly urbanizing desert cities (RUDC) around the globe experience an acute risk of flooding. To reduce this risk, properly engineered flood control structures (FCS) must account for sediment accumulation as well as flood waters. While the Phoenix area, USA, uses regional data from nonurban, non-desert watersheds to generate sediment yield rates, the proposed desired outcome for RUDCs is to base FCS on data related to urbanization. Wolman (1967 Geogr. Ann. A 49 385-95) recognized that sediment yields spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…A growing body of literature has suggested the effectiveness of management in mitigating and even reversing the deleterious impacts of urbanization. These practices include water infrastructure to counteract increased imperviousness (Bhaskar et al, 2020;Oudin et al, 2018) and store sediment (Jeong, 2019), as was demonstrated in central Arizona where retention basins decreased stream flashiness (McPhillips et al, 2019). Fountain Hills, therefore, may give a template for proactive management and geomorphic design (Chin & Gregory, 2009;Gregory & Chin, 2018) in guiding urbanizing dryland river systems towards stability.…”
Section: Implications and Discussionmentioning
confidence: 99%
“…A growing body of literature has suggested the effectiveness of management in mitigating and even reversing the deleterious impacts of urbanization. These practices include water infrastructure to counteract increased imperviousness (Bhaskar et al, 2020;Oudin et al, 2018) and store sediment (Jeong, 2019), as was demonstrated in central Arizona where retention basins decreased stream flashiness (McPhillips et al, 2019). Fountain Hills, therefore, may give a template for proactive management and geomorphic design (Chin & Gregory, 2009;Gregory & Chin, 2018) in guiding urbanizing dryland river systems towards stability.…”
Section: Implications and Discussionmentioning
confidence: 99%
“…The 18 stock pond watersheds (Figures 2 and 3) are located on pediments and fans with a variety of rock types (Figure 3). Urban sprawl in the Sonoran Desert (Figure 2) increased the region's vulnerability to erosion through construction, exposing bare ground to rainfall and runoff [32,55].…”
Section: Study Areamentioning
confidence: 99%
“…The stakes associated with urbanization-enhanced soil erosion tend to be spatially variable, as is the case for all soil erosion [19,31,109]. For example, the effects of urban soil erosion in the Phoenix area are relatively minor-impacting such issues as reservoirs [55], water quality [110], and health effects from heavy metals [111]. In other cities, soil erosion can impact the urban poor in a variety of ways, including a negative health impact [112] and water quality [113].…”
Section: Urbanization's Acceleration Of Erosionmentioning
confidence: 99%